Making Urban Schools Better Places for Students, Teachers, and Families: An Interview With Charles Payne - Teale, William H.; Scott, Jerrie L. (The Reading teacher, 2010)
By titling his 2008 book about urban school reform So Much Reform, So Little Change, Charles Payne summed up the feelings of many educators. Although the school reform movement has been active nearly two decades and has gone through various phases of implementing policies and practices, there appears to be little overall significant improvement in urban student achievement or school environments during that time. Intrigued by his perspectives on reform in urban schools, the editors of the Urban Literacy department conducted an interview with Payne, hoping to broaden their ideas about how to approach change in urban settings. بواسطة إلقاء عنوان على كتابه الذي صدر عام 2008 بشأن إصلاح المدارس المدنية إصلاحات كثيرة تغييرات قليلة استطاع تشارلز باين تلخيص أحاسيس معلمين كثيرين. ومع أن حركة إصلاح المدرسة كانت فاعلة لمدة عقدين من الزمن وقد مرت بمراحل متنوعة من السياسات والممارسات التنفيذية فهناك قليل من التحسنات المهمة التي حصلت في إنجاز الطالب المدني أو بيئات المدرسة في ذلك الوقت. وألفتت مناظره بشأن الإصلاحات في المدارس المدنية انتباه محرري قسم التعلم المدني لذا أجروا مقابلة مع باين في أمل توسيع أفكارهم تجاه الطريقة لإثارة التغيير في السياقات المدنية. 作者查尔斯．佩恩在2008年出版《太多改革，太少改变》一书时，以其书名概括了许多教育工作者对城市学校改革的感想。虽然城市学校改革运动已活跃近20年，并经历了政策与实践各个阶段的实施，但是在这20年当中，城市学生的成绩及学校的环境，在整体上似乎没有得到显着的改善。佩恩对城市学校改革的观点，引起了「城市读写教学」部门中的编辑的兴趣，因此与佩恩作了一个访谈，藉此希望扩阔其对如何处理城市教学环境转变之看法。 En intitulant son livre sur la réforme dans les écoles des quartiers défavorisés publié en 2008 Tant de réformes, si peu de changements, Charles Payne a résumé les sentiments de nombreux pédagogues. Quoique le mouvement de la réforme scolaire ait été actif pendant près de vingt ans et soit passé par diverses phases d'implantation de politiques et de pratiques, il semble s'être produit dans l'ensemble peu de progrès pendant tout ce temps en ce qui concerne la réussite des élèves des quartiers défavorisés ou l'environnement scolaire. Назвав свою книгу о реформировании городских школ, обслуживающих малоимущие слои населения, “Много шума из ничего” (So Much Reform, So Little Change, 2008), Чарльз Пейн выразил чувства многих педагогов. Школьная реформа продолжается уже почти два десятка лет, позади различные ее стадии – и в плане образовательной политики, и в плане методов осуществления реформ, однако успеваемость школьников существенно не повысилась и обстановка в городских школах не улучшилась. Редакторы рубрики взяли интервью у Чарльза Пейна, надеясь прояснить перспективы реформирования городских школ. Как добиться качественных изменений в образовании для учащихся из малоимущих и социально незащищенных слоев населения? Con el título Tantas reformas, tan poco cambio (So Much Reform, So Little Change), Charles Payne captó, en su libro de 2008 sobre reformas en las escuelas urbanas, los sentimientos de muchos educadores. Aunque el movimiento de reforma escolar ya ha cumplido veinte años y ha pasado por varias fases de implementación de pólizas y prácticas, no parece haber un mejoramiento significante en los logros de los estudiantes urbanos o en el medioambiente escolar. Sintiendo interés por sus perspectivas sobre la reforma en las escuelas urbanas, los editores del departamento de Urban Literacy entrevistaron a Payne con la esperanza de expandir sus ideas sobre cómo abordar cambios en las escuelas urbanas.